The Role of Service Quality and Digital Promotion on Customer Loyalty Café Meine Welt Palangka Raya, Central Kalimantan - Noorjaya Nahan; Abdi, Muhamad Ruzaini (International Journal of Contemporary Sciences (IJCS), 2024)
Research in the field of Marketing focuses on Service Marketing and applying digital marketing to increase Customer Loyalty. This research is based on the Dynamic Capability theory which indicates that a business unit to be able to survive must be evaluated and make business strategies that are relevant to the dynamics of business change. The research was conducted at the Café Meine Weltz in Palangka Raya City with 150 consumers as a benchmark and analyzed using the SPSS 22 statistical program. The results prove that the important role of service quality and knowledge sharing is to increase customer loyalty, which is 79.3%. The implications of the results can be a reference for Café Meine Weltz business actors, and can become a global reference for business actors at cafés in the city of Palangka Raya. Future research can adopt research indicators to increase market orientation in the culinary business